BHINNEKA TUNGGAL IKA DAN KONFLIK SOSIAL; (KHAZANAH MULTIKULTURAL INDONESIA DI ERA POST TRUTH) - Muhammad Usman; Masduki Duryat; H. Moch Sholeh; Fahmi Arfan; Muchsin; Faisal; Ikramullah Zein (Jurnal Sociohumaniora Kodepena (JSK), 2021)
Indonesia is one of the largest multicultural countries in the world, this can be seen from the sociocultural and geographical conditions of Indonesia that are so complex, diverse and broad. As a plural and heterogeneous country, Indonesia has the potential for multi-ethnic, multicultural, and multi-religious wealth, all of which are potentials to build a large multicultural nation "multicultural nation-state". This nation-state multicultural can be double charged; integration or conflict, which must be held together with full wisdom and nuances of tasamuh in the midst of society. As we understand together, the formation of the State of Indonesia on the basis of its country was formulated with a long and bloody struggle until it was proclaimed on August 17, 1945. The proclamation was also preceded by a long debate about the shape of the country - given the reality of Indonesia's plurality as a nation. as the foundation of the State, with the motto of Unity in Diversity. The effort for Indonesia to survive as a multicultural country continues to be carried out mainly by strengthening education (religion). Because education is believed to have a strategic role to build and restore the way of thinking and attitudes of students into a level that understands pluralism in society